UPAYA MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH MENENGAH PERTAMA MELALUI PENDEKATAN OPEN ENDED - Mikrayanti Mikrayanti (Program Studi Pendidikan Matematika, 2019)
ABSTRACT This research was motivated by the problem of the low learning outcomes of students of Bima City Middle School 6. To overcome this problem, research was conducted using the Open-ended approach. This study examines the problem of improving student learning outcomes. This research is a Classroom Action Research which consists of two cycles, in which each cycle consists of four stages, namely planning, action, observation and evaluation, and reflection. Data analysis was carried out quantitatively and qualitatively. Quantitative analysis is done by using student learning outcomes data. Qualitative analysis is done using the results of the observation sheet during the teaching and learning process. From the results of data processing, the percentage of learning completeness in the first cycle was 83% with an average value of 82.08, while the percentage of learning completeness in the second cycle was 92% with an average value of 86.67. The average score of student learning activities in cycles I and II was 3.46 and 3.89 with the active category. The results showed that students were more active and motivated in the teaching and learning process and there was an increase in student learning outcomes in each cycle using the Open-ended approach. Keywords: Open-ended and learning outcomes. This research was motivated by the problem of the low learning outcomes of students of Bima City Middle School 6. To overcome this problem, research was conducted using the Open-ended approach. This study examines the problem of improving student learning outcomes. This research is a Classroom Action Research which consists of two cycles, in which each cycle consists of four stages, namely planning, action, observation and evaluation, and reflection. Data analysis was carried out quantitatively and qualitatively. Quantitative analysis is done by using student learning outcomes data. Qualitative analysis is done using the results of the observation sheet during the teaching and learning process. From the results of data processing, the percentage of learning completeness in the first cycle was 83% with an average value of 82.08, while the percentage of learning completeness in the second cycle was 92% with an average value of 86.67. The average score of student learning activities in cycles I and II was 3.46 and 3.89 with the active category. The results showed that students were more active and motivated in the teaching and learning process and there was an increase in student learning outcomes in each cycle using the Open-ended approach. Keywords: Open-ended and learning outcomes.